The Transformation of Crisis Communication in Indonesian Mass Media during the Post-Truth Era - Krisno, Muhammad; Budiman, Dwi Aji; Al-Nahari, Yusra Hamed (Universitas Telkom, 2025)
This study aims to analyze how Indonesian mass media adapt to the communication crisis triggered by the post-truth era. Through a comprehensive literature review, it was found that both conventional and digital mass media in Indonesia are increasingly influenced by the dominance of opinion and emotion, which often replace factual information in the delivery of news. The post-truth era encourages media outlets to tailor their content to audience preferences, focusing more on sensational or emotionally charged news that aligns with personal beliefs, rather than presenting objective and verified information. A significant consequence of this shift is the widespread dissemination of hoaxes and misinformation, which are frequently published without adequate verification processes. Despite efforts by media outlets to adopt technological solutions and collaborate with fact-checking organizations, the spread of misinformation remains challenging to control. This study also highlights the ongoing shift in media communication strategies, which, although boosting audience engagement, increases the risk of sensationalism and the distribution of inaccurate information. Public trust in Indonesian mass media remains low, particularly among younger audiences who are heavily exposed to information through social media, which further exacerbates the communication crisis. The study concludes that the post-truth phenomenon contributes to growing social polarization, requiring a more holistic approach to address these issues. Collaboration between media organizations, the government, and society at large is essential to improving digital literacy and effectively combating the spread of misinformation.